Effect of Cooking Methods on Bioactivity of Polyphenols in Purple Potatoes - Qi Sun; Min Du; Duroy A. Navarre; Meijun Zhu (MDPI AG, 2021)
Purple-fleshed potato (Solanum tuberosum L.) is a good dietary source of anthocyanins, flavonols, and polyphenolic acids, mostly chlorogenic acid. The objective of this study was to examine the impacts of cooking methods including boiling, steaming, and the newly developed vacuum-sealed boiling (VSBoil) on extractability and bioactivity of polyphenolic compounds in a purple potato (PP) cultivar, Purple Pelisse. Data showed that boiling and steaming reduced the total polyphenolic content in PP. High-performance liquid chromatography analysis showed that steaming slightly reduced the extractable chlorogenic acid content, while VSBoil increased it. For DPPH free radical scavenging activities, VSBoil and steaming effectively preserved the antioxidant activity of a polyphenol-rich extract of PP, while boiling resulted in a significant reduction compared to raw potato extract. All extracts effectively suppressed bursts of intracellular reactive oxygen species in human colonic epithelial cells upon hydrogen peroxide induction, of which the extract from the VSBoil group showed the highest antioxidant potential. In addition, all extracts showed anti-inflammatory effects in Caco-2 cells induced with tumor necrosis factor-α. In conclusion, the content and bioactivity of extractable polyphenols were largely retained in PP subjected to different cooking processes. VSBoil resulted in the highest content of extractable polyphenolic compounds and bioactivity among tested cooking methods.